Chronology and order of tootheruption of permanentdentition in Villa Clara province, Cuba - Armando San Miguel Pentón; Olga Lidia Véliz Concepción; Lisette Ortega Romero (Editorial Ciencias Médicas, 2023)
Introduction: In Cuba thestandards of order and chronology of dental budding, used as a reference, are foreign. Objective: To describe thepatterns of theorder and chronology of outbreak of permanentdentition in Villa Clara province, Cuba. Methods: Anepidemiological and descriptivestudy of permanentdentition in Villa Clara, between 2015 and 2018 wasconducted. Bymeans of simple randommultistagesampling, a sample of 2064 girls and boysbetween 4 and 14 yearsold, born in Villa Clara, withoutalterations in general and craniofacialgrowth, wasobtained. In themtheoutbreakwasobserved and weightedaveragesforageswerecalculated. Results: Differenceswerefoundforagesaccordingto Mayoral, Moyers and Aguila. Symmetrypredominated in more than 50 % and thelowerteetheruptedbeforetheiruppercounterparts, with a frequency of 48.26 %, thelowercanineseruptedafterthelowerfirst premolar. Conclusions: Teethingsymmetrypredominated and occurred in separatetoothgroups, restingperiods and in a polymorphicorder. A tablewiththetootheruptionagesforthepopulation of Villaclarawascreated.